Infeksi Cacing pada Ular Kobra (Naja sputatrix) di Bali (WORM INFECTION ON SPITTING COBRA SNAKE (Naja Sputatrix) IN BALI) - Sismami, Dyah Ayu; Oka, Ida Bagus; Dharmawan, Nyoman Sadra (Jurnal Veteriner; Vol 15 No 3 (2014), 2014)
It has been done the survey for study about worm infection on spitting cobra snake (Naja sputatrix) inBali. There were 15 fecal samples from wild spitting cobra snake in Bali. The examination was usingconcentration cediment method. The result of examination showed that from all 15 fecal samples containedthe worm egg. From the result it could be conclude that the prevalent worm infection on spitting cobrasnake in Bali is capability 100% . From this study it means that infectioned could be happen more than 1(multiple infection) on 1 splitting cobra snake. The kind and prevalent of worm infected snake wereRhabdias sp (60,03%), Strongyloides sp (60,03%), Oxyuris sp (53,3%), Kalicephalus spp (20,01%), danCapilaria sp (6,67%). For enrich the information of another kind of parasitic infection should be done theresearch with variable and more collected samples.
Keywords: worm infection, spitting cobra snake, Bali